Localized mechanical stress induces time-dependent actin cytoskeletal remodeling and stiffening in cultured airway smooth muscle cells - Deng, L.; Fairbank, Nigel Jack; Fabry, Ben; SMITH, PAUL M.; Maksym, Geoffrey N. (American Journal of Physiology-Cell Physiology, 2004)
Mechanical stress (MS) causes cytoskeletal (CSK) and phenotypic changes in cells. Such changes in airway smooth muscle (ASM) cells might contribute to the pathophysiology of asthma. We have shown that periodic mechanical strain applied to cultured ASM cells alters the structure and expression of CSK proteins and increases cell stiffness and contractility (Smith PG, Moreno R, and Ikebe M. Am J Physiol Lung Cell Mol Physiol 272: L20-L27, 1997; and Smith PG, Deng L, Fredberg JJ, and Maksym GN. Am J Physiol Lung Cell Mol Physiol 285: L456-L463, 2003). However, the mechanically induced CSK changes, altered cell function, and their time courses are not well understood. Here we applied MS to the CSK by magnetically oscillating ferrimagnetic beads bound to the CSK. We quantified CSK remodeling by measuring actin accumulation at the sites of applied MS using fluorescence microscopy. We also measured CSK stiffness using optical magnetic twisting cytometry. We found that, during MS of up to 120 min, the percentage of beads associated with actin structures increased with time. At 60 min, 68.1 ± 1.6% of the beads were associated with actin structures compared with only 6.7 ± 2.8% before MS and 38.4 ± 5.5% in time-matched controls (P < 0.05). Similarly, CSK stiffness increased more than twofold in response to the MS compared with time-matched controls. These changes were more pronounced than observed with contractile stimulation by 80 mM KCl or 10 -4 M acetylcholine. Together, these findings imply that MS is a potent stimulus to enhance stiffness and contractility of ASM cells through CSK remodeling, which may have important implications in airway narrowing and dilation in asthm
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.lpmt.locali
Keywords: Actin cytoskeleton; Airway constriction and dilation; Airway smooth muscle cell; Asthma; Mechanical stress; Optical magnetic twisting cytometry; Stiffness